2004
DOI: 10.1029/2003jb002528
|View full text |Cite
|
Sign up to set email alerts
|

Fault mechanisms of induced seismicity at the superdeep German Continental Deep Drilling Program (KTB) borehole and their relation to fault structure and stress field

Abstract: [1] One hundred twenty-five fault plane solutions for microearthquakes induced during a long-term fluid injection experiment at the German Continental Deep Drilling Program (KTB) boreholes (Germany) in 2000 are investigated. A predominant strike-slip mechanism is observed, partly with components of normal but also with reverse faulting. Adding 54 fault plane solutions of an earlier injection experiment at the KTB, we determine the local stress field and find a subhorizontal north-south orientation for the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…They observe a direct relation between the size of earthquakes inverted (M>3) and homogeneity of the stress field determined. This phenomenon was also observed for fluid-injection induced seismicity at lower (-2<M<1) magnitude range (Bohnhoff et al, 2004). However, the data base of fault mechanisms from the Hellenic subduction zone give no indication for a similar relation which might be due to the smaller number of intermediate-sized (M~3) events which is explained by low seismic activity compared to other subduction zones.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…They observe a direct relation between the size of earthquakes inverted (M>3) and homogeneity of the stress field determined. This phenomenon was also observed for fluid-injection induced seismicity at lower (-2<M<1) magnitude range (Bohnhoff et al, 2004). However, the data base of fault mechanisms from the Hellenic subduction zone give no indication for a similar relation which might be due to the smaller number of intermediate-sized (M~3) events which is explained by low seismic activity compared to other subduction zones.…”
Section: Discussionmentioning
confidence: 78%
“…We do not discuss the stress tensor inversion techniques here in detail but refer to the relevant articles where the methods themselves and their applications are entirely discussed (e.g. Gephart and Forsyth, 1984;Gephart, 1990;Michael, 1987;Michael, 1991;Hardebeck and Hauksson, 2001;Bohnhoff et al, 2004). The inversion result for the entire catalogue reveals a well-constrained NS orientation for the maximum principal stress (σ 1 ) at shallow dipping angle.…”
Section: Stress Tensor Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the static stress drop is increasing with seismic moment. In a similar experiment at the same site six years later (Baisch et al, 2002;Bohnhoff et al, 2004) the seismic network detected 2799 events (-1.2 <M L < 1.1). 237 events had a sufficient signal-to-noise ratio at the surface stations to determine reliable hypocenters.…”
mentioning
confidence: 96%
“…Borehole breakouts, borehole fractures (Brudy et al, 1997;Zoback et al, 2003;Haimson, 2007), microseismic events (Shapiro et al, 1997;Baisch & Harjes, 2003;Bohnhoff et al, 2004;Michelet & Toksöz, 2007) and stimulation pressures (Zoback & Harjes, 1997;Legarth et al, 2003;Legarth et al, 2005) have been evaluated to confine the orientation and amplitude of the principal stress components.…”
Section: General Conceptsmentioning
confidence: 99%